(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the essence of scientific knowledge from the position of philosophical analysis. Its social nature is revealed, the causes and sources of the emergence of scientific thought are determined, and the functional aspects of scientific knowledge are determined. In this regard, an analysis of the relationship between philosophy and other natural and social sciences is given, the role and place of philosophical knowledge in the system of natural science and social and humanitarian knowledge is determined. They are also considered from the position of philosophical analysis of the relationship between knowledge and education, their dialectical continuity and differences. The structure of scientific knowledge associated with the levels of consciousness is revealed. Namely, the everyday, sensory-empirical in essence, and the theoretical, abstract-logical, levels of individual and social consciousness.